Overlaps of private sector with public sector around the globe - Kensinger, John W. (Research in finance ;, 2015)
The volume starts with the trends in bank deposits (and hence available financial resources) in the region around North Dakota's Bakken Formation oil reserves. Then comes a contribution analyzing how various regulatory uncertainties are undermining real estate investment. We have a study of corporate governance and firm performance for companies listed on the Indian Exchange, plus an ex-dividend analysis of emerging country stocks listed on the Dhaka Stock Exchange (DSE), where the tax rate is higher on dividends than on capital gains. Further analysis of dividend policy includes a study of how executives manage dividend growth in companies included in the Dow Jones Industrial Average and the NASDAQ Index (with data from 1989 into 2011). Also on the global stage we have analysis of systemic risk and financial contagion in Morocco. Then we also have an analysis of hedge fund performance. We also have analysis of share price response to operating cash flow in corporate bankruptcies. In the quantitative arena we have an application of the IZO Model (using a principal component approach), and improved empirical estimation of option volatility.